Специфіка долаючої поведінки у взаємозв’язках з толерантністю до невизначеності засуджених чоловіків - Шиліна, А. А.; Shylina, A. A.; Скляров, О. М.; Skliarov, O. M.; Шиліна Алла Андріївна (Право і безпека. – 2018. – № 4 (71). – С. 157-162, 2018)
Представлено результати дослідження толерантності до невизначеності та долаючої поведінки засуджених чоловіків, які відбувають покарання першим і не першим строками. У групах досліджуваних виявлено окремі статистично значущі відмінності між стратегіями долаючої поведінки, а також значущі кореляційні взаємозв’язки між окремими стратегіями та показниками інтолерантності.

It has been noted that a person during the execution of a sentence encounters other ways of life, culture, customs and attitudes towards him. Important psychological mechanisms that allow a convicted person to survive in difficult social conditions, to adapt to imprisonment, are strategies of overcoming behavior and tolerance to uncertainty. Tolerance to uncertainty allows the convicts to overcome easily the tension that arises in connection with expectations of constant novelty and changes. The author of the article has presented the results of the study of tolerance to uncertainty and overcoming behavior of convicted men, who serve punishment for the first time and those who not. Ways of Coping Questionnaire (R. Lazarus and S. Folkman in the adaptation of L. I. Wasserman) and New Questionnaire on Tolerance to Uncertainty by T. Kornilova were used for the pilot study. The t-criterion Student for independent groups and the Spearman correlation analysis were used for mathematical and statistical processing. It has been revealed that convicts who serve sentences not for the first time more often use strategies of distancing, self-control and responsibility. Instead, the convicts who serve first sentences manifest the relationship between the level of intolerance and the distancing strategy. The growth of intolerance of convicts who serve the punishment not for the first term, leads to the propensity to overcome the problem through intellectual methods of rationalization, switching attention, removal, humor, depreciation.

Представлены результаты исследования толерантности к неопределённости и совладающего поведения осуждённых мужчин, отбывающих наказание первым и не первым сроками. В группах испытуемых были обнаружены отдельные статистически значимые различия между стратегиями совладающего поведения, а также значимые корреляционные взаимосвязи между отдельными стратегиями и показателями интолерантности.
Specificity of overcoming behavior within relationship to tolerance to uncertainty of convicted men
Специфика совладающего поведения во взаимосвязях с толерантностью к неопределённости осуждённых мужчин
Keywords: Психологія. Рsychology. Психология; Юридична психологія. Legal psychology. Юридическая психология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; долаюча поведінка; копінг; толерантність до невизначеності; інтолерантність; засуджені чоловіки; overcoming behavior; coping; tolerance to uncertainty; intolerance; sentenced men; совладающее поведение; копинг; толерантность к неопределённости; интолерантность; осуждённые мужчины